Modified carbonized bamboo composite material and preparation method and application thereof

Through the preparation method of modified carbonized bamboo composite materials, the problem of slow reaction speed of metal-air battery cathode catalysts and scarcity of precious metal catalysts is solved, and efficient, stable and economical electrode catalytic performance is achieved.

CN119833652APending Publication Date: 2025-04-15BAOJI UNIV OF ARTS & SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510301862.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The slow oxygen kinetic reaction speed and high overpotential of existing metal-air battery cathode catalysts lead to limited application, and precious metal catalysts are scarce, expensive and have low durability.

Method used

Modified carbonized bamboo composite material is used as the electrode catalyst, and modified carbonized bamboo composite material is prepared by activating and carbonizing the bamboo raw material, and then ultrasonic impregnating and pyrolysis in the dispersion of metal-organic frame material.

Benefits of technology

It improves the catalytic performance of the electrode, enhances stability and durability, reduces production costs, and is rich in materials and low in price.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833652A_ABST
    Figure CN119833652A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of air batteries, and particularly relates to a modified carbonized bamboo composite material and a preparation method and application thereof. According to the method, bamboo is used as a raw material to prepare carbonized bamboo, on one hand, the bamboo has high carbon yield, the obtained carbonized bamboo has rich pore structures, ideal interconnected and ordered mass transfer and electron channels can be provided, and meanwhile, the carbonized bamboo is stable in structure, high in mechanical strength and good in toughness and can serve as a self-supporting base body; therefore, when the obtained modified carbonized bamboo composite material is used as an electrode, the modified carbonized bamboo composite material has relatively good stability and durability. Furthermore, the metal organic framework material is loaded on the carbonized bamboo, so that active sites in the composite material can be enriched, the intrinsic activity can be improved, the transfer of electrons can be promoted, and the catalytic performance of the composite material can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal-air batteries, and in particular relates to a modified carbonized bamboo composite material and a preparation method and application thereof. Background Art

[0002] In energy storage devices, electrical energy is a clean and efficient energy source. In order to generate, store, transmit and use electrical energy, electrochemical energy conversion and storage devices of different time scales and dimensions are required. Batteries can effectively convert and store electrical energy, so they are needed in many applications, from portable electronic devices to grid-scale energy storage and electric vehicles. Among the commonly used batteries are lithium-ion batteries and fuel cells. Lithium-ion batteries have insufficient energy density, insufficient safety and high cost. Fuel cells have high technical barriers, are not environmentally friendly and have high costs, while metal-air batteries have high theoretical energy density, are green and environmentally friendly, have high safety and low cost. Therefore, metal-air batteries are considered to be one of the most promising energy storage technologies and conversion devices.

[0003] However, the slow oxygen kinetics and high overpotential of cathode catalysts in metal-air batteries have become bottlenecks for their widespread application. Currently, Pt-based noble metals are considered to be the most advanced catalysts for HER, HOR and ORR, and Ir and Ru-based oxides also show good performance in OER. However, the scarcity, high price and low durability of these noble metals hinder their widespread application in the above-mentioned electrochemical redox reactions. In addition, transition metal-based catalysts and carbon-based catalysts have received widespread attention in recent years. However, due to limited active sites, poor intrinsic activity and stability, slow mass transfer and other issues, their electrocatalytic performance needs to be further improved.

[0004] Therefore, there is an urgent need for an electrode catalyst with good stability, rich active sites, good intrinsic activity and rapid mass transfer to further improve the catalytic performance. Summary of the invention

[0005] The purpose of the present invention is to provide a modified carbonized bamboo composite material and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a modified carbonized bamboo composite material, comprising the following steps: The bamboo raw material is activated and carbonized in sequence to obtain carbonized bamboo; The carbonized bamboo is ultrasonically immersed in a dispersion containing a metal organic framework material, and then pyrolyzed to obtain the modified carbonized bamboo composite material; The metal framework material includes a cobalt-based metal organic framework material, a zinc-based metal organic framework material or a zinc-indium-based metal organic framework material.

[0007] Preferably, the activation comprises: placing the bamboo material in an alkali solution for ultrasonic immersion; The alkali solution includes potassium hydroxide solution or sodium hydroxide solution; the mass concentration of the alkali solution is 10-30%; The ultrasonic immersion time is 6 to 24 hours; After the ultrasonic soaking, the soaked bamboo raw material is sequentially cleaned and dried.

[0008] Preferably, the carbonization temperature is 600-900°C, the heating rate is 2-5°C / min, and the holding time is 1.5-3.5h; The carbonization is carried out under a protective atmosphere.

[0009] Preferably, the cobalt-based metal organic framework material includes one or more of Zif-67, Zif-9, Zif-12 and Zif-21; The zinc-based metal organic framework material includes one or more of Zif-1, Zif-2, Zif-3, Zif-4, Zif-6, Zif-7, Zif-8, Zif-10, Zif-11, Zif-20, Zif-22, Zif-23, Zif-68, Zif-70 and Zif-95; The zinc-indium based metal organic framework material includes Zif-5.

[0010] Preferably, the mass concentration of the metal organic framework material in the dispersion containing the metal organic framework material is 15-30 g / L; The mass ratio of the carbonized bamboo to the dispersion containing the metal organic framework material is 1:100-120.

[0011] Preferably, the ultrasonic immersion time is 12 to 36 hours.

[0012] Preferably, the pyrolysis temperature is 600-900°C, the heating rate is 2-5°C / min, and the holding time is 2-3h; The pyrolysis is carried out under a protective atmosphere.

[0013] The present invention also provides a modified carbonized bamboo composite material prepared by the preparation method described in the above technical solution, comprising carbonized bamboo and metal and nitrogen loaded on the carbonized bamboo; The metal includes Co, Zn, or a combination of Zn and In.

[0014] Preferably, the metal loading mass percentage on the modified carbonized bamboo composite material is 0.5-20%; The nitrogen loading mass percentage on the modified carbonized bamboo composite material is 0.5-20%.

[0015] The present invention also provides the use of the modified carbonized bamboo composite material described in the above technical solution as an electrode in an air battery.

[0016] The invention provides a preparation method of a modified carbonized bamboo composite material, comprising the following steps: activating and carbonizing a bamboo raw material in sequence to obtain carbonized bamboo; ultrasonically impregnating the carbonized bamboo in a dispersion containing a metal organic framework material, and then pyrolyzing the carbonized bamboo to obtain the modified carbonized bamboo composite material; the metal framework material comprises a cobalt-based metal organic framework material, a zinc-based metal organic framework material or a zinc-indium-based metal organic framework material.

[0017] The present invention uses bamboo as a raw material to prepare carbonized bamboo. On the one hand, the bamboo has a high carbon yield, and the obtained carbonized bamboo has a rich pore structure, which can provide ideal interconnection and orderly mass transfer and electron channels. At the same time, the carbonized bamboo has a stable structure and high mechanical strength and good toughness, and can be used as a self-supporting matrix, so that the obtained modified carbonized bamboo composite material has good stability and durability when used as an electrode. Furthermore, the present invention loads the metal organic framework material on the carbonized bamboo, which can enrich the active sites in the composite material, improve the intrinsic activity, and promote the transfer of electrons, thereby improving the catalytic performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The XRD patterns of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1; Figure 2 This is a SEM image of the modified carbonized bamboo composite material obtained in Example 1 before pyrolysis; Figure 3 The Raman graphs of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1; Figure 4 TEM image and HRTEM image of the modified carbonized bamboo composite material obtained in Example 1; Figure 5 This is the XPS graph of the modified carbonized bamboo composite material obtained in Example 1; Figure 6 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams of the modified carbonized bamboo composite material and carbonized bamboo obtained in Example 1; Figure 7 ORR LSV diagrams of the modified carbonized bamboo composite materials obtained in Examples 1 to 3, carbonized bamboo, and the commercially available Pt / C catalyst in Comparative Example 1; Figure 8 The OER LSV diagrams of the modified carbonized bamboo composite materials obtained in Examples 1 to 3, the carbonized bamboo, and the commercially available Ir / C catalyst in Comparative Example 1; Fig. 9The charge and discharge cycle curves of the modified carbonized bamboo composite material obtained in Example 1 and the commercially available Pt / C+Ir / C catalyst in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0019] The present invention provides a method for preparing a modified carbonized bamboo composite material, comprising the following steps: The bamboo raw material is activated and carbonized in sequence to obtain carbonized bamboo; The carbonized bamboo is ultrasonically immersed in a dispersion containing a metal organic framework material, and then pyrolyzed to obtain the modified carbonized bamboo composite material; The metal framework material includes a cobalt-based metal organic framework material, a zinc-based metal organic framework material or a zinc-indium-based metal organic framework material.

[0020] The invention activates and carbonizes bamboo raw materials in sequence to obtain carbonized bamboo.

[0021] In the present invention, the size of the bamboo material is preferably 1 cm (tangential)×4 cm (lateral)×0.25 cm (vertical).

[0022] In the present invention, the activation preferably includes: placing the bamboo material in an alkali solution for ultrasonic immersion. In the present invention, the alkali solution preferably includes potassium hydroxide solution or sodium hydroxide solution; the mass concentration of the alkali solution is preferably 10-30%; the ultrasonic immersion time is preferably 6-24 hours, and more preferably 12 hours. In the present invention, after the ultrasonic immersion, it is also preferably included to sequentially wash and dry the soaked bamboo material. In the present invention, the washing preferably includes sequentially performing deionized water ultrasonic washing and ethanol ultrasonic washing; the number of deionized water ultrasonic washing and ethanol ultrasonic washing is preferably 2 times. In the present invention, the drying temperature is preferably 80°C, and the time is preferably 12 hours.

[0023] In the present invention, the carbonization temperature is preferably 600-900°C, specifically 600°C, 700°C, 800°C, 900°C, the heating rate is preferably 2-5°C / min, the holding time is preferably 1.5-3.5h, more preferably 2h; the carbonization is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen.

[0024] After obtaining the carbonized bamboo, the present invention ultrasonically immerses the carbonized bamboo in a dispersion containing a metal organic framework material, and then pyrolyzes the carbonized bamboo to obtain the modified carbonized bamboo composite material.

[0025] In the present invention, the metal framework material includes a cobalt-based metal organic framework material, a zinc-based metal organic framework material or a zinc-indium-based metal organic framework material; the cobalt-based metal organic framework material preferably includes one or more of Zif-67, Zif-9, Zif-12 and Zif-21; the zinc-based metal organic framework material preferably includes one or more of Zif-1, Zif-2, Zif-3, Zif-4, Zif-6, Zif-7, Zif-8, Zif-10, Zif-11, Zif-20, Zif-22, Zif-23, Zif-68, Zif-70 and Zif-95; the zinc-indium-based metal organic framework material preferably includes Zif-5.

[0026] In the present invention, the Zif-67 is preferably obtained by preparation, and the preparation method preferably comprises: Dissolve Co(NO3)2·6H2O in methanol to obtain a cobalt salt solution; Dissolve 2-methylimidazole in methanol to obtain a ligand solution; The ligand solution is added dropwise to the cobalt salt solution and allowed to stand for reaction to obtain the Zif-67.

[0027] In the present invention, the dosage ratio of the Co(NO3)2·6H2O and methanol is preferably 6.552 g:50 mL; the dissolution of the Co(NO3)2·6H2O in methanol is preferably carried out under stirring, and the stirring time is preferably 20 min.

[0028] In the present invention, the dosage ratio of the 2-methylimidazole and methanol is preferably 7.938g:100mL, and the 2-methylimidazole is preferably dissolved in methanol under stirring, and the stirring time is preferably 20min. In the present invention, the standing reaction time is preferably 4h. In the present invention, after the standing reaction, it is also preferred to centrifuge the reaction system and wash the obtained solid, and the washing preferably includes sequentially performing deionized water ultrasonic washing and ethanol ultrasonic washing; the number of deionized water ultrasonic washing and ethanol ultrasonic washing is preferably 2 times.

[0029] In the present invention, the mass concentration of the metal organic framework material in the dispersion containing the metal organic framework material is preferably 15-30 g / L, specifically 15 g / L, 18 g / L, 20 g / L, 22 g / L, 24 g / L, 26.67 g / L, 30 g / L; the mass ratio of the carbonized bamboo to the dispersion containing the metal organic framework material is preferably 1:100-120, specifically 1:100, 1:110, 1:113.7, 1:115, 1:120.

[0030] In the present invention, the ultrasonic impregnation time is preferably 12 to 36 hours, more preferably 24 hours. In the present invention, after the ultrasonic impregnation, the impregnated material is preferably dried, and the drying temperature is preferably 60° C. and the drying time is preferably 12 hours.

[0031] In the present invention, the temperature of the pyrolysis is preferably 600-900°C, specifically 600°C, 700°C, 800°C, 900°C, the heating rate is preferably 2-5°C / min, more preferably 3-4°C / min, and the holding time is preferably 2-3h; the pyrolysis is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen. In the present invention, the pyrolysis process can promote further condensation, cross-linking, isomerization and dehydration reactions of the carbonized bamboo, and at the same time, the metal ions in the metal organic framework material are reduced to a single substance at high temperature, and then converted into a self-supporting carbon material loaded with metal active sites.

[0032] The present invention also provides a modified carbonized bamboo composite material prepared by the preparation method described in the above technical solution, comprising carbonized bamboo and metal and nitrogen loaded on the carbonized bamboo; the metal comprises Co, Zn or a combination of Zn and In.

[0033] In the present invention, the weight percentage of the metal on the modified carbonized bamboo composite material is preferably 0.5-20%; the weight percentage of the nitrogen on the modified carbonized bamboo composite material is preferably 0.5-20%.

[0034] The present invention also provides the use of the modified carbonized bamboo composite material described in the above technical solution as an electrode in an air battery.

[0035] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0036] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1 The bamboo raw material was cut into bamboo pieces of 1 cm (tangential) × 4 cm (transverse) × 0.25 cm (vertical). The bamboo pieces were ultrasonically soaked in a 10% KOH solution for 12 h, and then ultrasonically cleaned twice with deionized water and anhydrous ethanol respectively; dried in a drying oven at 80 °C for 12 h, and then heated to 900 °C at a heating rate of 5 °C / min in a nitrogen atmosphere for pyrolysis, and kept warm for 2 h to generate carbonized bamboo (denoted as CB); Co(NO3)2·6H2O (6.552 g) was dissolved in 50 mL of methanol and stirred for 20 min to obtain a cobalt salt solution. 2-Methylimidazole (7.938 g) was dissolved in 100 mL of methanol and stirred for 20 min to obtain a ligand solution. The obtained ligand solution was added dropwise to the cobalt salt solution, and the reaction was allowed to stand for 4 h. The generated solid was centrifuged and then ultrasonically cleaned twice with deionized water and anhydrous ethanol to obtain Zif-67.

[0038] 0.8 g of the obtained Zif-67 was added to 30 mL of methanol to form an impregnation solution, and the carbonized bamboo was immersed in the impregnation solution and ultrasonicated for 24 hours. The carbonized bamboo after impregnation was then taken out and dried in a drying oven at 60° C. for 12 hours. The dried sample was placed in a porcelain boat, and the temperature was increased to 900° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for pyrolysis, and the temperature was kept for 2 hours to obtain the modified carbonized bamboo composite material (denoted as Co-N@CB), in which the loading mass percentage of Co was 8.3% and the loading mass percentage of nitrogen was 2.7%.

[0039] Example 2 The modified carbonized bamboo composite material was prepared in the same manner as in Example 1, except that the pyrolysis temperature was 700° C. The loading mass percentage of Co was 7.2%, and the loading mass percentage of nitrogen was 2.2%.

[0040] Example 3 The modified carbonized bamboo composite material was prepared in the same manner as in Example 1, except that the pyrolysis temperature was 800° C. The loading mass percentage of Co was 7.5%, and the loading mass percentage of nitrogen was 2.4%.

[0041] Comparative Example 1 Commercially available Pt / C, Ir / C.

[0042] Performance Testing Test Example 1 The modified carbonized bamboo composite material obtained in Example 1 was characterized; Figure 1 The XRD patterns of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1 are shown in Table 1. Figure 1 It can be seen that there are two obvious diffraction peaks at 44.22° and 51.52°, corresponding to the (111) and (200) crystal planes of Co, respectively.

[0043] Figure 2 This is the SEM image of the modified carbonized bamboo composite material obtained in Example 1 before pyrolysis. Figure 2 It can be seen that the ZIF-67 with a regular dodecahedral structure is loaded in the pore structure of carbonized bamboo.

[0044] Figure 3 The Raman graphs of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1 are shown in FIG. Figure 3 It can be seen that 1354cm -1 and 1584cm -1 The two different characteristic peaks correspond to the D band and the G band. The D band represents the structural defects in the carbon lattice, and the G band represents the degree of graphitization. The intensity ratios of ID / IG of carbonized bamboo and modified carbonized bamboo composites are 0.971 and 0.941, respectively, indicating that the addition of Co increases the crystallinity of carbon and reduces the lattice defects of carbon. High graphitization is the key to conductivity.

[0045] Figure 4 The TEM image (left) and HRTEM image (right) of the modified carbonized bamboo composite material obtained in Example 1. Transmission electron microscopy (TEM) shows that ZIF-67 is loaded in the pore structure of carbonized bamboo. The self-supporting structure of carbonized bamboo makes the loaded MOFs more uniform, and its natural pores are conducive to the diffusion and transfer of electrolyte ions and oxygen molecules. Carbonized bamboo with an integral structure can be directly used as an air electrode for liquid ZABs without any binder. High-resolution transmission electron microscopy (HRTEM) images show that the lattice distance of Co particles is 0.209nm, corresponding to the (111) crystal plane of Co.

[0046] Figure 5 This is the XPS graph of the modified carbonized bamboo composite material obtained in Example 1, where the left graph is the C1s graph, the middle graph is the N1s graph, and the right graph is the Co 2P graph. The XPS spectrum shows the presence of C, N, and Co elements. The XPS spectrum of C1s shows two peaks at 284.8 and 285.6 eV, which correspond to C=C and CC / CN, respectively. The high-resolution N1s spectrum shows three N substances, represented by graphitic nitrogen (401.9 eV), pyrrolic nitrogen (401 eV), and pyridinic nitrogen (399.2 eV). Pyridinic nitrogen increases the starting potential of the redox reaction, and graphitic nitrogen determines the diffusion limiting current of the redox reaction. The high-resolution Co 2p spectrum is divided into eight peaks. The peaks at 781 and 795.6 eV correspond to Co 0 2p 3 / 2 and Co 0 2p 1 / 2 The peaks at 781.3 and 797.1 eV correspond to Co 3+ 2p 3 / 2 and Co 3+ 2p 1 / 2 At 783 eV (Co 2+ 2p 3 / 2 ) and 798.7eV (Co 2+ 2p 1 / 2The two peaks at 786.8 and 802 eV are due to the presence of divalent cobalt, confirming the formation of Co-N sites. The addition of Co-N bonds can improve the ORR and OER activities of the catalyst. The peaks at 786.8 and 802 eV are satellite peaks.

[0047] Figure 6 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1 are shown in FIG. The specific surface area of ​​the carbonized bamboo is 99.25 m 2 ·g -1 The specific surface area of ​​the modified carbonized bamboo composite material can reach 451.14m 2 ·g -1 , catalysts with large specific surface areas can provide more active sites, which can promote the transfer of reactants and increase the redox reaction rate.

[0048] Test Example 2 The ORR performance of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Examples 1 to 3 and the commercially available Pt / C catalyst in Comparative Example 1 was tested. The test method was as follows: the ORR performance was tested in an oxygen-saturated, 0.1 M KOH solution at a rotation speed of 1600 rpm; The test results obtained are as follows Figure 7 As shown in Table 1; Table 1 Half-wave potential of modified carbonized bamboo composite material obtained in Example Figure 7 The ORR LSV diagrams of the carbonized bamboo, modified carbonized bamboo composite materials obtained in Examples 1 to 3 and the commercially available Pt / C catalyst in Comparative Example 1 are shown in FIG. Figure 7 It can be seen that the half-wave potentials of carbonized bamboo, modified carbonized bamboo composites and Pt / C catalyst are 0.7 V, 0.81 V, 0.77 V, 0.78 V and 0.84 V, respectively. The half-wave potential of the modified carbonized bamboo composite is close to that of the commercial electrocatalyst Pt / C.

[0049] Test Example 3 The OER performance of the carbonized bamboo and modified carbonized bamboo composite materials obtained in Example 1 and the commercially available Ir / C catalyst in Comparative Example 1 was tested. The test method is as follows: In 1M KOH electrolyte, the OER performance is tested using a three-electrode system. The test results are as follows: Figure 8 As shown in Table 2; Table 2 Overpotential of modified carbonized bamboo composite materials obtained in Example Figure 8 The OER LSV diagrams of the carbonized bamboo, modified carbonized bamboo composite material obtained in Examples 1 to 3 and the commercially available Ir / C catalyst in Comparative Example 1 are shown in FIG. Figure 8 It can be seen that carbonized bamboo, modified carbonized bamboo composites and Ir / C catalysts have good thermal conductivity at a current density of 10 mA cm -2 The overpotentials at different OER times are 1.573 V, 1.384 V, 1.5 V, 1.45 V, and 1.535 V, respectively. The overpotential of the modified carbonized bamboo composite material is better than that of Ir / C. The lower the OER overpotential, the better the catalytic performance of the catalyst, which can more efficiently carry out electrochemical redox reactions, reduce energy consumption, and improve energy conversion efficiency.

[0050] Test Example 4 The modified carbonized bamboo composite material obtained in Example 1 and the commercially available Pt / C+Ir / C catalyst in Comparative Example 1 were used as test samples to test the battery performance, wherein the mass ratio of Pt / C to Ir / C in Comparative Example 1 was 1:1; Test method: With zinc sheet as anode, test sample as cathode, and electrolyte as 100mL containing 6M KOH and 0.2M zinc acetate, the battery performance was tested using the Blue Battery Test System. The test results are as follows: Fig. 9 As shown; Fig. 9 The charge-discharge cycle curves of the modified carbonized bamboo composite material obtained in Example 1 and the commercially available Pt / C+Ir / C catalyst in Comparative Example 1 are shown in FIG. Fig. 9 It can be seen that the modified carbonized bamboo composite material and the commercial Pt / C+Ir / C catalyst have a -2 At a current density of 1.34 W / m, the charge and discharge cycle time is 1583 h and 49 h respectively. The charge and discharge time of the modified carbonized bamboo composite material is much longer than that of the Pt / C+Ir / C catalyst.

[0051] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified carbonized bamboo composite material, characterized in that: The following steps are involved: The bamboo raw material is activated and carbonized in sequence to obtain carbonized bamboo; The carbonized bamboo is ultrasonically immersed in a dispersion containing a metal organic framework material, and then pyrolyzed to obtain the modified carbonized bamboo composite material; The metal framework material includes a cobalt-based metal organic framework material, a zinc-based metal organic framework material or a zinc-indium-based metal organic framework material.

2. The preparation method according to claim 1, characterized in that: The activation comprises: placing the bamboo material in an alkali solution for ultrasonic immersion; The alkali solution includes potassium hydroxide solution or sodium hydroxide solution; the mass concentration of the alkali solution is 10-30%; The ultrasonic immersion time is 6 to 24 hours; After the ultrasonic soaking, the soaked bamboo material is sequentially cleaned and dried.

3. The preparation method according to claim 1, characterized in that: The carbonization temperature is 600-900°C, the heating rate is 2-5°C / min, and the holding time is 1.5-3.5h; The carbonization is carried out under a protective atmosphere.

4. The preparation method according to claim 1, characterized in that: The cobalt-based metal organic framework material includes one or more of Zif-67, Zif-9, Zif-12 and Zif-21; The zinc-based metal organic framework material includes one or more of Zif-1, Zif-2, Zif-3, Zif-4, Zif-6, Zif-7, Zif-8, Zif-10, Zif-11, Zif-20, Zif-22, Zif-23, Zif-68, Zif-70 and Zif-95; The zinc-indium based metal organic framework material includes Zif-5.

5. The preparation method according to claim 1, characterized in that: The mass concentration of the metal organic framework material in the dispersion containing the metal organic framework material is 15-30 g / L; The mass ratio of the carbonized bamboo to the dispersion containing the metal organic framework material is 1:100-120.

6. The preparation method according to claim 1 or 5, characterized in that: The ultrasonic immersion time is 12 to 36 hours.

7. The preparation method according to claim 1, characterized in that: The pyrolysis temperature is 600-900°C, the heating rate is 2-5°C / min, and the holding time is 2-3h; The pyrolysis is carried out under a protective atmosphere.

8. The modified carbonized bamboo composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: comprising carbonized bamboo and metal and nitrogen supported on the carbonized bamboo; The metal includes Co, Zn, or a combination of Zn and In.

9. The modified carbonized bamboo composite material according to claim 8, characterized in that: The metal loading mass percentage on the modified carbonized bamboo composite material is 0.5-20%; The nitrogen loading mass percentage on the modified carbonized bamboo composite material is 0.5-20%.

10. Use of the modified carbonized bamboo composite material according to claim 8 or 9 as an electrode in an air battery.

Citation Information

Patent Citations

  • Forest-derived air electrode material as well as preparation method and application thereof

    CN113381031A

  • SDS-treated mangosteen shell-based porous carbon loaded Ni-Co-O nanoparticle material as well as preparation method and application thereof

    CN115312328A

  • Modified biochar composite material as well as preparation method and application thereof

    CN119018890A

  • Preparation method for co, n, and s co-doped carbon nano-bead composite material and use thereof

    WO2023137840A1